Severity of Child Autistic Symptoms and Parenting Stress in Mothers of Children with Autism Spectrum Disorder in Japan and USA: Cross-Cultural Differences. (12th July 2022) - Porter, Noriko; Loveland, Katherine A.; Saroukhani, Sepideh; Posey, Yana; Morimoto, Kana; Rahbar, Mohammad H.
Abstract : The purpose of this study was to compare the relationship between parenting stress and autistic symptom severity in the U.S. and Japan. Fifty-two U.S. and 51 Japanese mothers of children aged 2–12 with autism completed measures of parenting stress and child characteristics, including the parenting stress index (PSI), the social communication questionnaire (SCQ), and social responsiveness scale-2 (SRS-2). There was a nonlinear relationship between the child's autistic symptom severity and parenting stress in both countries. We also found some cultural differences: in the parent domain, the relationships between children's SCQ scores and PSI scores differed significantly between the U.S. and Japan. Our findings suggest that autistic severity symptom scores may reflect cross-cultural differences in parenting beliefs, views toward autism, and response styles for evaluating children's behavior. The findings also suggest that parents need support regardless of the child's autism severity, including those with mild to moderate symptoms. Expanding on this line of research and understanding cultural influences on parenting stress may help service providers and agencies offer more culturally sensitive services, parent-education courses, and intervention programs.